2021
DOI: 10.52852/tcncyh.v141i5.211
|View full text |Cite
|
Sign up to set email alerts
|

Study on clinical and genetic characteristics of male patients with non-obstructive azoospermia

Abstract: We examined 501 patients with non - obstructive azoospermia to evaluate clinical, subclinical, and genetic characteristics. The results show that the average age of patients in the study was 29.8 ± 5.5 years. Primary infertility accounts for the majority, with a rate of 90.3%. There was 38.6% of patients had a history of mumps orchitis. The average levels of FSH, LH, testosterone were 31.6 ± 16.5 mIU/mL, 15.5 ± 10 mIU/mL and 12.8 ± 7.13 nmol/L, respectively. The prevalence of chromosomal abnormalities was 30.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…2 Data from Hanoi Medical University Hospital showed that azoospermia affected 20.8% of patients who sought consultation for male infertility at the Department of Andrology and Sexual Medicine. 3 Among the etiology of azoospermia, non-obstructive azoospermia (NOA) is the most severe form due to the failure of spermatogenesis and in the past, the only option for fathering a child is donor sperm. However, with the advances of assisted reproductive technique (ART) and microsurgery, the use of micro testicular sperm extraction (microTESE) followed by intracytoplasmic injection (ICSI) has brought the opportunity for these patients to have their own children.…”
Section: Introductionmentioning
confidence: 99%
“…2 Data from Hanoi Medical University Hospital showed that azoospermia affected 20.8% of patients who sought consultation for male infertility at the Department of Andrology and Sexual Medicine. 3 Among the etiology of azoospermia, non-obstructive azoospermia (NOA) is the most severe form due to the failure of spermatogenesis and in the past, the only option for fathering a child is donor sperm. However, with the advances of assisted reproductive technique (ART) and microsurgery, the use of micro testicular sperm extraction (microTESE) followed by intracytoplasmic injection (ICSI) has brought the opportunity for these patients to have their own children.…”
Section: Introductionmentioning
confidence: 99%